HUBUNGAN KEPATUHAN PENGOBATAN TERHADAP KUALITAS HIDUP PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS KEDUNGWUNGU BANYUWANGI - Auliya Honestly; Ahmad Suriyadi Muslim; Bintari Tri Sukoharjanti (Nusantara Hasana Journal, 2025)
Hypertension, or high blood pressure, is a degenerative condition often referred to as “The Silent Killer”, which medication adherence plays a crucial role in determining patients’ quality of life. Quality of life serves as an essential bechmark for individuals to evaluate their level of well-being. This study aimed to examine the relationship between medication adherence and quality of life among hypertensive patients in the working are of Kedungwungu Public Health Center, Banyuwangi. This research employed a quantitative design with data presented numerically. A cross-sectional approach was used with a correlational analytic method. Sampling was conducted using a convenience sampling technique involving 115 respondents. Data were collected using the MARS-5 questionnaire for medication adherence and the WHOQOL-BREF questionnaire for quality of life. The findings showed that most respondents had high adherence (68,69%), followed by moderate adherence (26,95%) and low adherence (4,34%). Quality of life scores were predominantly within the range of 76-100 (53,04%), followed by 60-75 (39,13%) and 0-59 (7,83%). Medication adherence was found to be positively and significantly associated with quality of life (r = 0,806; p<0,001). Patients with high adherence tended to have better quality of life. Whereas low adherence was consistently accompanied by poor quality of life. These findings emphasize that medication adherence is a key determinant og improved quality of life among hypertensive patients and may also be influenced by demographic characteristics such as marital status, occupation, and duration of illness.